2009
DOI: 10.1186/1476-4598-8-32
|View full text |Cite
|
Sign up to set email alerts
|

The role of cellular oxidative stress in regulating glycolysis energy metabolism in hepatoma cells

Abstract: Background: The Warburg effect has been found in a wide spectrum of human cancers, however the underlying mechanisms are still unclear. This study aims to explore the role of cellular oxidative stress in relation to glycolysis and the Warburg effect in hepatoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 42 publications
4
70
0
Order By: Relevance
“…Low molecular weight phosphate group carriers are common in energy transfer and maintenance, and therefore unusually high energy consumption upon TP treatment was suspected. Energy depletion together with the changed levels of GSH and NAD + lead us to hypothesize that the cells may be trying to counter oxidative stress caused by the peptide (Pereira et al, 1999;Shi et al, 2009). Therefore we showed that TP treatment indeed changes the GSH redox ratio and very significantly decreases cellular redox potential.…”
Section: Discussionmentioning
confidence: 82%
“…Low molecular weight phosphate group carriers are common in energy transfer and maintenance, and therefore unusually high energy consumption upon TP treatment was suspected. Energy depletion together with the changed levels of GSH and NAD + lead us to hypothesize that the cells may be trying to counter oxidative stress caused by the peptide (Pereira et al, 1999;Shi et al, 2009). Therefore we showed that TP treatment indeed changes the GSH redox ratio and very significantly decreases cellular redox potential.…”
Section: Discussionmentioning
confidence: 82%
“…In cells, most of the ATP is produced by two metabolic pathways: the aerobic oxidative phosphorylation in mitochondria and the anaerobic glycolysis in the cytoplasm. Oxidative stress has been shown to regulate glycolytic metabolism (Colussi et al, 2000;Grant, 2008;Shi et al, 2009). We therefore investigated whether a mutation in a CI subunit might lead to a metabolic switch between aerobic and anaerobic glycolytic pathways.…”
Section: Oxidative Stress Modulates Atp Production and Cell Growthmentioning
confidence: 99%
“…The cytotoxic selectivity of BZL101 for cancer cells as opposed to normal cells is based on the metabolic preferences of tumor cells, namely, intrinsically higher basal levels of reactive oxygen species (ROS) and dependence on glycolysis for energy production (Warburg effect) that make cancer cells significantly more vulnerable to BZL101-induced death [6]. Extensive studies to elucidate the mechanism of action of BZL101 have shown [4][5][6]: (a) BZL101 induces more ROS, and, correspondingly, greater DNA damage in tumor cells than in normal cells, (b) severe DNA damage in tumor cells leads to the hyperactivation of poly (ADP-ribose) polymerase (PARP) and depletion of its substrate NAD and ATP (PARP substrates), and (c) the depletion of NAD results in the inhibition of glycolysis and further decline in ATP because glycolysis is frequently the only energy-generating mechanism in tumor cells [7]. The collapse of redox and energy status is followed by programmed necrosis of tumor cells while normal cells repair DNA damage and continue to produce energy through mitochondrial respiration.…”
Section: Introductionmentioning
confidence: 99%